Instant coffee as a source of antioxidant-rich and sugar-free coloured compounds for use in bakery: Application in biscuits. (15th September 2017) - Passos, Cláudia P.; Kukurová, Kristína; Basil, Eva; Fernandes, Pedro A.R.; Neto, Andreia; Nunes, Fernando M.; Murkovic, Michael; Ciesarová, Zuzana; Coimbra, Manuel A.
Graphical abstract: Highlights: Instant coffee can be used as raw material to prepare sugar-free melanoidins (SFM). Ultrafiltration or ethanol precipitation are simple procedures to obtain SFM rich food ingredients. Biscuits supplemented with SFM fractions may be produced with different brown colours and/or caffeine contents. SFM fractions increased biscuits antioxidant properties without promoting acrylamide increase. The amount of 5-hydroxymethylfurfural (HMF) in coffee fractions decreases two thirds during biscuits baking. Abstract: Ammonia caramels are the most common antioxidant colour agent used in bakery formulations, although their high sugars content. An alternative could be coffee melanoidins, which are brown coloured compounds with antioxidant properties, readily available from instant coffee. However, high caffeine content is limiting its direct application. To evaluate the possibility of obtaining coloured melanoidin-rich, sugars- and caffeine-poor fractions from instant coffee, in this work, simple procedures based on their ethanol insolubility (fraction EtPp) or retention by ultrafiltration (fraction HWSn) were exploited. Melanoidins incorporation into biscuits formulation (amounts of 1, 5 and 10% w/w related to flour content) resulted in acceptable coloured products with higher antioxidant activity. The biscuits supplemented with 1% EtPp or HWSn had a low caffeine content. The caffeine of one espresso coffee was equivalent to 130 biscuits containing EtPp and 31 biscuits containing HWSn. Besides, both fractions did not promote extra formation of acrylamide or 5-hydroxymethylfurfural during baking.